Peculiarities of The Legal Regulation of the Digital Intellectual Economy Based on Supply Chain Management - Ksenia Michailovna Belikova (International Journal of Supply Chain Management, 2019)
This manuscript is dedicated to the study of the features of legal support for the functioning of the digital economy. The authors consider some reasons for the need to modernize legislation in the context of the development of the digital economy, as well as its concept and some of its features. Additionally, the authors studied various approaches to the legal regulation of the digital economy.